Keanekaragaman Tumbuhan Bawah di Kawasan Universitas Negeri Jakarta - Putri, Dwi Kurnia; Murnisari, Yunita; Madalena, Dea Kristia; Setiarini, Nelia; Diputri, Rimba Liewa Dinta; Suryanda, Ade; Azrai, Eka Putri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2024)
Understory plants are a group of plants that form a layer near the surface of the soil. One of the functions of undergrowth is as a ground cover which contributes to increasing the organic matter content in the soil. This research was conducted in November 2023 in the garden behind the KH. Hasyim Asy'ari Building, Jakarta State University. The aim of this research is to determine the diversity of understory plants found in the Jakarta State University environment. The research method used was a survey using a sampling technique with a quadratic method. There are 4 types of undergrowth in the garden behind the KH. Hasyim Asy'ari Building, namely Cyanthillium cineroum, Pilosela officinarum, Eclipta prostrata, and Cynodon dactylon. The results of the calculation of the Shannon-Wiener diversity index based on its classification show that the garden behind the KH. Hasyim Asy'ari Building, Jakarta State University has a low level of understory plant diversity.